Intergenerational poverty in Ireland - Sarah Curristan; Bertrand Maître; Helen Russell (The Economic and Social Research Institute (ESRI), 2022)
The impact of poverty is far-reaching, and it poses risks for an individual's health, educational attainment, employment prospects and broader wellbeing. Past research strongly indicates that individuals who experience poverty in childhood face an increased risk of experiencing poverty as adults; this is commonly termed the intergenerational transmission of poverty. Understanding the factors and pathways that link childhood and adult circumstances offers an opportunity to inform policies for addressing social disadvantage. This study explores persistence of poverty between generations in the Irish context. In doing so, it draws upon data gathered by the European Union Statistics on Income and Living Conditions (EU-SILC) survey special module on the 'intergenerational transmission of disadvantages'. This special module, which was administered in all EU countries in 2005, 2011 and 2019, asks respondents to retrospectively report on the financial circumstances they experienced within their home during childhood (aged approximately 14 years). Thus, our analysis concentrates on these three different cohorts to compare how financial circumstances in the home experienced during childhood may affect one's current financial situation. The module is administered in Ireland through the Survey of Income and Living Conditions (SILC).
Keywords: 330